Analisis Kualitas Pembelajaran dalam Implementasi Kurikulum Merdeka di SD Negeri Petompon 02 Semarang - Jesentika Wisanta Sari; Arfilia Wijayanti; Mira Azizah (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2024)
The implementation of the Independent Curriculum aims to enhance learning quality in Indonesia. At SD Negeri Petompon 02 Semarang, challenges include the need for differentiated teaching modules, lack of structured teacher coordination, low teacher motivation and competence, and high workloads. This study explores the quality of learning through classroom management, affective support, and cognitive activities, using a descriptive qualitative method. Findings highlight the significance of effective classroom management, consistent affective support, and engaging cognitive activities as benchmarks of learning quality. The principal plays a vital role in leading school development, while teachers are responsible for motivating and guiding students. Students demonstrate active participation and positive responses to the learning process. Despite these achievements, continuous evaluation and improvement remain necessary. This study underscores the need for synergy between principals, teachers, and students to achieve optimal learning quality aligned with the principles of the Independent Curriculum. Keywords: Learning Quality; Independent Curriculum; Classroom Management; Affective Support; Cognitive Activities.